1989
DOI: 10.1038/342940a0
|View full text |Cite
|
Sign up to set email alerts
|

Zfy gene expression patterns are not compatible with a primary role in mouse sex determination

Abstract: The Y chromosome determines maleness in mammals. A Y chromosome-linked gene diverts the indifferent embryonic gonad from the default ovarian pathway in favour of testis differentiation, initiating male development. Study of this basic developmental switch requires the isolation of the testis-determining gene, termed TDF in humans and Tdy in mice. ZFY, a candidate gene for TDF, potentially encodes a zinc-finger protein, and has two Y-linked homologues, Zfy-1 and Zfy-2, in mice. Although ZFY, Zfy-1 and Zfy-2 see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(103 citation statements)
references
References 18 publications
8
95
0
Order By: Relevance
“…Zfy is present in two copies in Mus musculus (Mardon et al 1989;Nagamine et al 1989) and has amplified up to 26 times on the Y chromosome in other rodents Lau et al 1992;Nagamine 1994). The two Mus musculus Zfy copies are expressed in the testis and do not appear to be functionally redundant (Koopman et al 1989). …”
Section: Discussionmentioning
confidence: 99%
“…Zfy is present in two copies in Mus musculus (Mardon et al 1989;Nagamine et al 1989) and has amplified up to 26 times on the Y chromosome in other rodents Lau et al 1992;Nagamine 1994). The two Mus musculus Zfy copies are expressed in the testis and do not appear to be functionally redundant (Koopman et al 1989). …”
Section: Discussionmentioning
confidence: 99%
“…Our conclusion that ZFY was the wrong gene was soon confirmed independently by the finding (by another young Australian, Peter Koopman, a postdoc in Robin Lovell-Badge's London laboratory), that ZFY was expressed in the germ cells of the mouse testis, but not in the somatic cells (Koopman et al 1989), where the sex determination signal had to be received.…”
Section: Marsupials and The Molecular Search For The Male-determiningmentioning
confidence: 81%
“…Although previously thought to have a function in testis determination, such a role has now been excluded [1][2][3]. It has been suggested that the Z f y l gene may have a function in spermatogenesis, perhaps as a transcription factor [4].…”
Section: Discussionmentioning
confidence: 99%
“…Although a primary role in sex determination has now been ruled out [2,3] the conservation of this gene on the Y chromosome of placental mammals suggests it has some important male-specific function, perhaps in spermatogenesis [4]. A gene closely related to ZFY, called ZFX, is also present on the X chromosome of all placental mammals so far analysed [4].…”
Section: Introductionmentioning
confidence: 99%